Sports technique key elements in phase structure of connecting moves of acrobatic exercises performed on a beam - Niznikowski, T.; Sadowski, J. (Theory and Practice of Physical Culture, 2019)
Objective. To study the kinematic structure of the key element indices of sports technique connecting move of acrobatic exercises round-off - salto backward tucked performed on a beam; to single out sports technique key elements in the phase structure of exercise connecting move. Material and methods. The study involved skilled and highly skilled female gymnasts (n = 16). Their average indices of height, body mass and age (x ± d) constituted 157.5 ± 2.85 cm; 51 ± 2.25 kg; 20 ± 2.35 years, respectively. Performance of the connecting move of acrobatic exercises round-off - salto backward tucked on a beam was recorded by two digital video cameras JVS 6R-DVL 9800 NTSC with shooting speed of 240 frames per second. Measurement error constituted 3%. APAS 2000 (Ariel Dynamice Inc.) computer program was used for analysis of motion joint angles, velocities, accelerations of joints and body GCM; time of exercise phase execution; method of motion postural landmarks. Results. Sports technique key elements in the phases of the connecting move of acrobatic exercises round-off - salto backward tucked performed on a beam were determined along with their indices: body launching posture (LP) during the round-off finishing - close to vertical stable body posture with narrow stand and legs apart, on tiptoe on support, with arms fore-upward, for efficient upward-backward flying up; phase of the main motor actions - multiplication of body postures (MP) "tucked" - active successive alternating instant fixed salto phases for creation of an integral motor action; during the phase of the final motor actions - concluding body posture (CP) - landing to stop. Conclusions. Sports technique key elements as the signal postures of motor actions combine the indices of phase structure of the connecting move of acrobatic exercises round-off - salto backward tucked, executed on a beam, through the interaction of previous and subsequent body postures and their multiplications. They are amenable to development and improvement. Performance of exercises without unnecessary motor rearrangements is achieved, thus avoiding the accumulation of technical faults in the process of demonstrating competitive exercises.